Facial Fractures in Young Adults: A National Retrospective Study. (June 2019) - Povolotskiy, Roman; Youssef, Pavly; Kaye, Rachel; Paskhover, Boris
Objectives: "Young adulthood" is a term used to define individuals falling within the 18- to 22-year-old age range. Injuries account for more than a third of emergency department visits in this population. A particular area of concern is accidents that lead to injuries of the facial bones because they can have long-term functional, aesthetic, and psychosocial impacts. As many as 30 million young adults participate in some sort of sport in the United States per year, and facial injuries from these activities are not uncommon and thus require further exploration. Methods: The National Electronic Injury Surveillance System was used to conduct a retrospective review to explore patterns of maxillofacial fractures in young adult patients between the ages of 18 and 22 years from 2004 through 2017. The data analyzed yielded information about patient demographics, diagnoses, and associated products. Results: A total of 3486 emergency department visits were included in the study. The most common facial fractures were nasal fractures (64.4%), mandible fractures (12.3%), and orbital fractures (6.1%). The most common causes of fractures were sports (55.48%), fixed structures (6.39%), and stairs or steps (5.60%). The top 3 sports associated with facial fractures were basketball (25.4%), baseball (11.6%), and football (10.4%). Conclusions: For young adult individuals, some sort of sporting activity is common outside of the National Collegiate Athletic Association. The overwhelming majority of facial fractures in this population were caused by sports, and the authors believe this issue warrants further exploration and discussion. According to the Centers for Disease Control and Prevention, an estimated 8.6 million sports- and recreation-related injuries occurred per year between 2011 and 2014. Despite ever growing research and guidelines into sports injury incidence and prevention, it is clear that sports are the cause of a large portion of maxillofacial fractures in the United States.